2002
DOI: 10.1139/z01-220
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous maturation of the sexes may limit close inbreeding in a subsocial spider

Abstract: We studied the temporal patterns of maturation and sexual receptivity of a subsocial spider, Anelosimus cf. jucundus, in southern Arizona. In subsocial spiders, sibling males and females share a common nest for a large portion of their life cycle, often only dispersing short distances close to the mating season. We found that, on average, male A. cf. jucundus matured 9 days earlier than females and that females did not become sexually receptive until 10 days following their final molt to maturity. The periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…Females of the subsocial spider Anelosimus arizona (formerly A. cf. jucundus) delay their sexual receptivity, maximising foraging after moulting (Bukowski and Aviles 2002). A similar period of little tactochemical attractiveness in early adult period (1st week after last moult) was indicated by Roberts and Uetz (2005) for S. ocreata females.…”
Section: Discussionmentioning
confidence: 78%
“…Females of the subsocial spider Anelosimus arizona (formerly A. cf. jucundus) delay their sexual receptivity, maximising foraging after moulting (Bukowski and Aviles 2002). A similar period of little tactochemical attractiveness in early adult period (1st week after last moult) was indicated by Roberts and Uetz (2005) for S. ocreata females.…”
Section: Discussionmentioning
confidence: 78%
“…We suggest that natal dispersal in this species primarily reflects competition for resources within the natal nest and that inbreeding avoidance, if present, is accomplished through alternative mean such as differences in maturation dates between sibling males and females combined with later movements of one or both sexes (Bukowski & Avile´s 2002). Anelosimus cf.…”
Section: Discussionmentioning
confidence: 91%
“…jucundus is morphologically close, but not identical to Anelosimus jucundus (O. P. Cambridge 1986), a subsocial species described from montane areas in Costa Rica, Panama, and Ecuador (Levi 1956(Levi , 1963I. jucundus in sourthern Arizona has been described in detail by Avile´s & Gelsey (1998); see also Bukowski & Avile´s 2002). comm.).…”
Section: Study Speciesmentioning
confidence: 99%
“…Because patch mates may consist of siblings (Lubin et al 1998, Johannesen and Lubin 1999, emigration would reduce the likelihood of mating with kin. Bukowski and Avilés (2002) suggested that asynchrony in maturation between sexes may limit inbreeding and also explain an apparent lack of discrimination of kin as mates in another subsocial spider, Anelosimus jucundus (Theridiidae). Dispersal patterns of A. jucundus were similar to S. lineatus, because a fraction of males were philopatric and mated locally whereas other males emigrated beyond the local area (Avilés and Gelsey 1998).…”
Section: Polyandry Protandry and Inbreeding Avoidancementioning
confidence: 99%